Aberrant expression of E-cadherin in infiltrating ductal and lobular breast carcinomas and its correlation with clinicopathological parameters – A hospital-based study - T, Shruthi; Dr. Ramesh Chavan; Dr. Naresh Jaikumar Kulkarni (Tropical Journal of Pathology and Microbiology, 2021)
Introduction: Breast carcinoma is one of the commonest malignant tumours in women, leading to premature deaths and morbidity. E-cadherin is a 120kDa calcium-dependent transmembrane glycoprotein encoded by the CDH1 gene located on chromosome 16q21 and is expressed in most epithelial cells. Loss of E Cadherin expression implies cell discohesion and favours metastasis. The study aims to evaluate the expression of E-cadherin in breast carcinoma and its association with various histomorphological and clinicopathological parameters. Materials and Methods : A total of 30 cases of breast carcinomas were studied, over two years. Histological grade and type were assessed by staining the paraffin-embedded sections with H & E. Using IHC technique, E-cadherin antigen was retrieved by Heat-Induced Epitome Retrieval method, and immunostaining was scored semiquantitatively. Cases were grouped as ‘preserved,’ when positivity was strong membranous, and occurred in more than 75% of the neoplastic epithelial cells and ‘aberrant’ in all the remaining cases. The scores were then correlated with the histopathological grade, histological type of tumour and clinicopathological parameters. Results: E-cadherin was found to be preserved in 46.7% of all the breast carcinomas and aberrant in 51.7% of invasive ductal carcinomas (IDC) alone, while 100% of invasive lobular carcinomas showed aberrant expression. No significant correlation was found with E-cadherin grading and histological type of carcinoma, histopathological grade or involvement of deep surgical margin. Conclusion: Differentiation between invasive ductal and invasive lobular carcinoma based on the loss of E-cadherin has to be done cautiously given its aberrant expression in ductal carcinomas as well.